Anthelmintic activity of Annona crassiflora leaves against Haemonchus contortus: part 2: efficacy in vivo and blood parameters - Caldeira, Marco Antonio Martins; Morais-Costa, Franciellen; Macêdo, Kaike Magno; Martins Júnior, Valdo Soares; Pereira, Dheison Emanuel Augusto; Soares, Ana Cláudia Maia; Martins, Isabela Parolis; Lopes, Idael Matheus Goes; Braga, Fernão Castro; Oliveira, Neide Judith Faria; Duarte, Eduardo Robson (Medicina Veterinária, 2020)
In this study we evaluated the oral toxicity of leaf extracts of Annona crassiflora of for mice and the blood and parasitological parameters of lambs experimentally infected with Haemonchus contortus and treated with leaves of this plant. The highest dose of AE (aqueous extract) administered to mice (203.0 mg/kg bw) was well tolerated, suggesting low toxicity. At necropsy, macroscopic examination revealed no abnormalities of the evaluated viscera.  Lambs infected with the nematode were divided one group treated with leaf powder and a control group that did not treat. Split-plot design analysis was performed where the treatments were defined as plots and three periods of collection were defined as subplots. Similar performances to weight gain were observed among the lamb groups. The oral administration of leaf powder at 2.75g /Kg bw did not alter the physiological blood parameters in comparison to untreated lambs; however, this dose was not efficient to fecal egg reduction.    We consider that other formulations and administration protocols should be evaluated to promote an effective alternative control using the leaves of this plant.